STUDY on THE FORMULATION of squid (Loligosp) NUGGET ADDED WITH YELLOW PUMPKIN (Curcubitamoschata) FLOUR - Lisa Nurharyati; Suparmi '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the squid nugget formulation with the addition of pumpkin flour. It was evaluated for the organoleptic value and the proximate composition. The method used was an experimental method and designed as non-factorial completely randomized design (CRD). The treatments were addition of pumpkin flour into the mix, consisting of four levels, namely: N0 (without the addition of pumpkin flour), N1 (pumpkin flour 50 g), N2 (pumpkin flour 75 g) and N3 (pumpkin flour 100 g).Based on the organoleptic value, proximate composition, and the fold test assed to squid nugget, the results showed that the best treatment was the addition of flour pumpkin amounted 75 gr. The characteristic was bright yellow (8.25), savory flavors (8.12), aroma of pumpkin flour was very smelt (8.17),and dense very compact and chewy texture, (8.15). It contained water (58.16%), protein (11.61%), fat (0.96%), ash (0.99%) and crude fiber (24.64%), and the score of the folding test (4.67).Keywords: Nugget, squid, pumpkin flour, formulation